PEMBUATAN INKUBATOR TELUR DENGAN ARDUINO SEBAGAI MIKROKONTROLER MENGGUNAKAN SISTEM INTERNET OF THINGS (IoT) - Andara Paulina; Masthura Masthura; Nazaruddin Nasution (Universitas Riau, 2023)
In the process of hatching eggs in poultry, stable temperature and humidity are needed so that the eggs can develop properly. Poultry eggs, especially chickens take 21 days to hatch with a temperature of 37°C – 39°C and humidity of 50% – 60%. The study aims to produce an incubator that is able to monitor temperature and humidty based on arduino microcontrollerswith an internet of things (IoT) system and determine the stability of temperature and humidity values in the incubator. Test were carried out by incubating 6 eggs in an incubator with the result that 5 eggs hatched perfectly and 1 other egg did not develop properly. The conditions of temperature and humidity during the hatching process are classifed as stable, namely termperatures between 37.34°C – 38.34°C and humidity between 52.80% – 56.40%. The system is able to read and send the readings of temperature and humidity sensor values to the Blynk aplication properly.